Quo Vadis Amandemen Konstitusi: Kebijakan Hukum Partisipatif-Populis Versus Representatif-Elitis - Partice Rondonuwu (Advokasi Hukum & Demokrasi (AHD), 2023)
Constitutional and governmental issues and problems occur by looking at the interests of the elite and the will of the people who want fundamental changes related to state life and government life which affect the overall life of a nation state. Indonesia is a very large nation state with a state government that is managed from Sabang to Merauke with various tribes, religions, races and groups that are full of diversity. State and government life is not free from various problems at the elitist and populist levels which are resolved by just and civilized constitutional and governmental mechanisms. One of the various ways to make changes to constitutional legal policy is by making constitutional amendments to the 1945 NRI Constitution. Constitutional amendments to the 1945 NRI Constitution can be seen in the elitist representative legal policy model and the participatory-populist legal policy model. The battle of issues and problems as well as solutions based on representative-elitist legal policy versus populist participatory legal policy will create positive things (constructive nation-building in all fields) and negative things (destructive constitutional movements that destroy the foundations of the unitary state). Anticipating the occurrence of negative things will make the constitutional amendment run smoothly and all parties can accept it openly.